The Effectiveness of Using the Role-Playing Strategy in the Achievementof Sixth Grade Students in Kurdish Grammar - Nasreen Mohammed Abdullah (Zanco Journal of Human Sciences, 2025)
The research aims at investigating the effectiveness of utilizing the Role Play strategy in the sixth grade students' achievement in Kurdish grammar. To achieve the objective of the study, a null hypothe have been constructed by the researcher. and they relied on the experimental design, with control and experimental groups by adopting a post-test to the variable academic achievement, the population of the study was limited to the sixth grade basic students for the academic year (2022-2023) of the Directorate of General Education, at schools (kreen and barez), which were chosen intentionally. The research sample was randomly chosen, which consists of (32) students in the experimental group, and (30) students in the control group.The equivalence between two groups was conducted in a number of variables, the researcher prepared one tool, which is the test to measure academic achievement, which consists of (35 questions, extracting the difficulty coefficient, discriminatory strength and the effectiveness of wrong alternatives. Conclusion , providing convincing explanation, proposed solution, the validity and reliability of the tool have been duly confirmed. After completing the application of the tools. The data has been obtained by using statistical means, by using the (T-Test). Result have been shown that using Role Play strategy in teaching Kurdish grammar subject has positive impact on increasing students’ academic achievement compared to the using traditional teaching metho In the light of the research results, the researcher recommended to concerned authorities, and suggested more future studies to complement the topic.